Distribution of Radiation Doses Received by Organs at Risk in Cervical Cancer Using Intracavitary Brachytherapy Technique - I Made Raditya Anandika Putra; Gusti Ngurah Sutapa; I Gde Antha Kasmawan; Ni Nyoman Ratini; I Made Satriya Wibawa; I Ketut Putra (Kappa Journal, 2025)
A study entitled Distribution of Radiation Doses Received by Organs at Risk in Cervical Cancer Using Intracavitary Brachytherapy Technique has been conducted. The study was conducted at the Radiotherapy Sub-Installation of Prof. Dr. I.G.N.G Ngoerah Hospital with the aim of determining the distribution of doses received by High Risk Clinical Target Volume (D2cc) and Organs at Risk (D90). Determining the distribution of doses received by High Risk Clinical Target Volume (D2cc) and Organs at Risk (D90) in cervical cancer patients is still within the recommended limits in ICRU Report 89. This study used ionizing radiation by inserting radioactive cobalt-60 using internal radiotherapy techniques, namely intracavitary brachytherapy. Before the irradiation process is carried out, there is a planning stage or Treatment Planning System (TPS). The reference for this research standard is for HRCTV of 95% -107% and for OAR bladder ≤80% rectum ≤75%. The average percentage of dose distribution received by HRCTV was 104.2% which is equivalent to 7.2 Gy which is still within the range of 95%- 107%, in the bladder it was 69.4% which is equivalent to 5.Gy which is still below the value ≤80%, and in the rectum it was 57% which is equivalent to 4.1 Gy which is still below the value ≤75%. The dose distribution value in HRCTV and OAR was still within the tolerance limit listed in the recommended value in GEC-ESTRO-ABS, and ICRU Report 89.